2016
DOI: 10.4317/jced.52682
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of root caries among elders living in residential homes of Bengaluru city, India

Abstract: BackgroundAmong the various oral ailments which have been observed in elderly, root caries is a significant one. Tooth loss is chief oral health-related negative variable to the quality of life in elderly and root caries is the major cause of tooth loss in them. It has been reported about a third of older population bears most of the root caries burden, so the present study aimed to assess the prevalence of root caries among older individuals residing in residential homes of Bengaluru city India.Material and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 25 publications
3
15
2
Order By: Relevance
“…The included studies reported caries prevalence or experience of older adults at the age of 60 or above in 20 countries from six continents (Table 1). Most of them were conducted in Asia (n = 20, China [11][12][13][14][15][16], India [17][18][19][20][21][22][23][24], Singapore [25], Turkey [26][27][28][29][30][31][32][33][34][35][36][37][38] and Vietnam [29,30]) and Europe (n = 10, Finland [31], Germany [32,33], Ireland [34], Kosovo [35], Norway [36], Poland [37,38], Portugal [39] and Romania [40]). There were three studies conducted in North America (Mexico [41,42] and USA [43]), one in South America (Brazil [44]), two in Oceania (Australia [45,46]) and three in Africa (...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies reported caries prevalence or experience of older adults at the age of 60 or above in 20 countries from six continents (Table 1). Most of them were conducted in Asia (n = 20, China [11][12][13][14][15][16], India [17][18][19][20][21][22][23][24], Singapore [25], Turkey [26][27][28][29][30][31][32][33][34][35][36][37][38] and Vietnam [29,30]) and Europe (n = 10, Finland [31], Germany [32,33], Ireland [34], Kosovo [35], Norway [36], Poland [37,38], Portugal [39] and Romania [40]). There were three studies conducted in North America (Mexico [41,42] and USA [43]), one in South America (Brazil [44]), two in Oceania (Australia [45,46]) and three in Africa (...…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies (28/39) were conducted on community dwellers in community setting. The rest were carried out in residential homes or day centres (10 studies [13,14,16,17,19,20,30,39,41,42]). One study was hospital-based [25].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations